2020
DOI: 10.1024/1661-8157/a003498
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Teaching in der Ultraschall-Ausbildung – Eine Übersichtsarbeit

Abstract: Zusammenfassung. Ultraschall wird zunehmend zu einem wichtigen Lerninhalt bereits im Medizin-Studium. Die Vermittlung ist jedoch sehr zeitaufwändig, weshalb viele Universitäten Peer-Teaching in der Ultraschallausbildung einsetzen. Peer-Teaching hat verschiedene Vorteile, die über das blosse Einsparen von Ausbildungsstunden rarer Fachkräfte hinausgehen: Studierende lernen von Mitstudierenden unter Umständen besser, weil ihre kognitiven Schemata kongruenter sind und sie Peers gegenüber eher ihre Lerndefizite off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…We found one study on cardiac ultrasound with a larger sample of 88 participants that showed superiority of near-peer teachers [5]. In most cases, the format for teaching near-peer courses is the same as for faculty courses [3,[5][6][7][8]. Course evaluations [9], observations of near-peer teaching [10], psychological models [2] and our study team's practical experience [11] highlight several advantages of near-peer teaching: Near-peers are socially closer to trainees and may be more aware of students' problems [2], even though they have less clinical experience and content expertise than faculty teachers [2,4].…”
Section: Introductionmentioning
confidence: 98%
“…We found one study on cardiac ultrasound with a larger sample of 88 participants that showed superiority of near-peer teachers [5]. In most cases, the format for teaching near-peer courses is the same as for faculty courses [3,[5][6][7][8]. Course evaluations [9], observations of near-peer teaching [10], psychological models [2] and our study team's practical experience [11] highlight several advantages of near-peer teaching: Near-peers are socially closer to trainees and may be more aware of students' problems [2], even though they have less clinical experience and content expertise than faculty teachers [2,4].…”
Section: Introductionmentioning
confidence: 98%